Self-assessment of active learning and critical thinking during problem-based learning: an exploratory study - Kiran Fatima Mehboob Bana; Muhammad Shahid Shamim; Zeelaf Shahid (Journal of the Pakistan Medical Association, 2022)
Objective: To assess whether problem-based learning enhances students’ perception of their active learning and critical thinking skills with time, and to validate the self-assessment scale regarding active learning and critical thinking in the local context. Method: The exploratory study was conducted at the Bahria University Dental College, Karachi, from February to September 2020, and comprised dental undergraduates in their first and second years of the academic programme Data was collected using the self-assessment scale on active learning and critical thinking questionnaire which was administered twice after problem-based learning tutorials. Data was analysed using SPSS 23. Results: There was a significant difference in the mean questionnaire scores of modules 1 and 3 of the first-year batch and modules 4 and 6 of the second-year batch (p=0.001). Cronbach’s alpha value was 0.735 in the first-year cohort and 0.802 in the second-year cohort. Conclusion: Dental students’ perception of active learning and critical thinking increased with time using problem-based learning as the tool. The self-assessment scale on active learning and critical thinking was also found validated in the local context. Key Words: Active learning, Critical thinking, Dental undergraduates, Problem-based learning, PBL, Self-assessment.